'Playing the Judicial Card': Litigation Strategies during the Process of Ratification of the Lisbon Treaty. Issue 5 (30th September 2013) - Castillo Ortiz, Pablo José
Abstract During the process of ratification of the Lisbon Treaty, a number of constitutional jurisdictions were activated by political actors. In playing 'the judicial card', opponents of ratification decided to seek political goals through judicial means, and thus they were obliged to develop litigation strategies. This article explores such strategies and the responses that courts gave them. It shows that constitutional proceedings with regards to the Lisbon Treaty became a political battleground governed by legal logics, in which the interpretation of European clauses, the democratic deficit of the Union and the tensions underlying the European judicial dialogue were privileged objects of discussion between claimants and courts in which law and politics intertwined.